HUMAN RESOURCE PLANNING IN THE UTILIZATION OF COCONUT SHELLS AS RENEWABLE ALTERNATIVE FUEL - Jeheo, Lyan; Hamdi, Edi; Negoro, Dimas Angga; Sunaryanto, Ketut (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
The use of coconut shells as a renewable alternative fuel has great potential to support the clean energy transition and environmental sustainability. As one of the largest coconut producing countries in the world, Indonesia has abundant resources that can be processed into energy products such as briquettes, charcoal, and bioenergy. However, the success of this utilization requires mature human resource (HR) planning to ensure the availability of competent workers, high productivity, and empowerment of local communities. This study aims to analyze the strategic role of HR planning in supporting the development of the coconut shell-based fuel industry. The method used involves a descriptive-qualitative approach, which includes identifying workforce needs, developing training, and collaborative strategies between the government, private sector, and local communities. Effective HR planning can increase the efficiency of the production process, open new jobs, and empower rural communities. In addition, synergy between stakeholders is key to creating a sustainable work ecosystem. Thus, the use of coconut shells as an alternative fuel not only contributes to reducing carbon emissions but also encourages local economic growth